2004
DOI: 10.1212/01.wnl.0000130531.90205.ef
|View full text |Cite
|
Sign up to set email alerts
|

Memory impairment, but not cerebrovascular disease, predicts progression of MCI to dementia

Abstract: Background-Mild cognitive impairment (MCI) is widely viewed as the transition phase between normal aging and Alzheimer disease (AD). Given that MCI can also result from cerebrovascular disease (CVD), the authors used clinical, MRI, and cognitive measures of AD and CVD to test the hypothesis that CVD increases the likelihood of progression from MCI to dementia within 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
190
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(205 citation statements)
references
References 60 publications
15
190
0
Order By: Relevance
“…In addition, MCI subjects with greater hippocampal atrophy at baseline are more likely to convert to AD (Jack et al, 1999;Visser et al, 1999;Killiany 2000;Dickerson et al, 2001;Killiany et al, 2002;Adak et al, 2004;DeCarli et al, 2004). In this study however, hippocampal volumes at baseline in APOE ∈4 carriers treated with donepezil (5062 mm 3 , SD 773 mm 3 ) were not different from those treated with placebo (4916 mm 3 , SD 744) (p= 0.51) ( Table 1).…”
Section: Effect Of Treatment On Mri Atrophy Ratesmentioning
confidence: 50%
See 1 more Smart Citation
“…In addition, MCI subjects with greater hippocampal atrophy at baseline are more likely to convert to AD (Jack et al, 1999;Visser et al, 1999;Killiany 2000;Dickerson et al, 2001;Killiany et al, 2002;Adak et al, 2004;DeCarli et al, 2004). In this study however, hippocampal volumes at baseline in APOE ∈4 carriers treated with donepezil (5062 mm 3 , SD 773 mm 3 ) were not different from those treated with placebo (4916 mm 3 , SD 744) (p= 0.51) ( Table 1).…”
Section: Effect Of Treatment On Mri Atrophy Ratesmentioning
confidence: 50%
“…This is consistent with other longitudinal MRI studies (Hashimoto et al, 2005) as well as a large body of literature on the biologic effect of APOE ∈4 indicating that carriers have an increased probability of developing AD and an increased likelihood of converting from MCI to AD than non carriers (Corder et al, 1993;Petersen et al, 1995). Studies evaluating the relationship between APOE ∈4 status and brain morphometry have found effects consistent with greater disease severity, an independent contribution of APOE ∈4 and atrophy to clinical disease severity, and greater likelihood of clinical progression in APOE ∈4 carriers (Plassman et al, 1997;den Heijer et al, 2002;Adak et al, 2004;DeCarli et al, 2004;Farlow et al, 2004;Fleisher et al, 2005). The effect of APOE ∈4 on MRI rates observed in this MRI sub study is consistent with the results in the main treatment study in which APOE ∈4 carriers in each treatment group (donepezil, vitamin E, and placebo) were more likely to convert to AD than non carriers.…”
Section: Discussionmentioning
confidence: 98%
“…Cognitive impairment without dementia, as defined in the present study, is a broad classification [41] with a high prevalence in diabetes [42]. Mild cognitive impairment is a more restrictive category with a high rate of transition to dementia, but it has recently been shown that the subgroup of mild cognitive impairment associated with CVD is less likely to progress to dementia [43]. Follow-up studies will be required to determine whether these patients will progress to dementia.…”
Section: Discussionmentioning
confidence: 79%
“…Whether this is a generalizable finding, however, requires further study. For example, the research on the comparative value of imaging and cognitive predictors of conversion from MCI to dementia, a change defined in part by decreasing everyday function, is quite mixed (DeCarli et al, 2004;Korf et al, 2004;Visser et al, 1999).…”
Section: Discussionmentioning
confidence: 99%